2009
DOI: 10.1007/s00259-009-1203-0
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT imaging in primary osseous and soft tissue sarcomas: a retrospective review of 212 cases

Abstract: The combined metabolic and morphological information of FDG PET/CT imaging allows high sensitivity for the detection of various sarcomas and accurate discrimination between newly diagnosed low-grade and high-grade sarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 15 publications
6
118
1
2
Order By: Relevance
“…The SUVmax, MTV, and TLG were demonstrated to be prognostic factors for predicting OS. In previous reports, the SUVmax on pretreatment 18 F-FDG PET/CT could be used to discriminate between low-and high-grade soft tissue sarcomas [37,38]. In this study, pathologic tumor responder and non-responder groups were discriminated not only by the SUVmax, but also by MTV and TLG.…”
Section: Discussionmentioning
confidence: 71%
“…The SUVmax, MTV, and TLG were demonstrated to be prognostic factors for predicting OS. In previous reports, the SUVmax on pretreatment 18 F-FDG PET/CT could be used to discriminate between low-and high-grade soft tissue sarcomas [37,38]. In this study, pathologic tumor responder and non-responder groups were discriminated not only by the SUVmax, but also by MTV and TLG.…”
Section: Discussionmentioning
confidence: 71%
“…A review of 212 patients of sarcomas (both osseous and softtissue sarcomas) revealed the mean SUVmax value of the primary and/or the most avid metastatic lesion in the positive cases to range from 5.6 to 23.2 (median, 9.9), with most lesions having an SUVmax .2.5. 29 Another study of 109 patients revealed SUVmax of the primary tumour to range from 1.7 to 35.8 (median, 7.7). 30 The definite role of PET/CT needs further clarification but mainly lies in evaluating patients for metastases, for assessing response to treatment and in detecting recurrent disease.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 1,310 articles screened, 16 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) were selected for the final analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%